1999
DOI: 10.1046/j.1365-8711.1999.02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the 3.3- m UIR band in the Red Rectangle: relation to unidentified optical emission

Abstract: A B S T R A C TThe biconical Red Rectangle nebula exhibits very strong unidenti®ed infrared (UIR) emission bands, a subset of the optical diffuse interstellar bands (in emission) and extended red emission (ERE). A key question is the extent to which the carriers of these spectroscopic signatures may be related. In a new study of the 3.3-mm emission, CGS 4 spectra were recorded at UKIRT, which give information on the spatial distribution of the 3.3-mm carrier in the nebula and on the width, peak wavelength and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 51 publications
(58 reference statements)
1
37
0
Order By: Relevance
“…Polarization maps by Perkins et al (1981) suggested that the spikes are produced by dust scattering at dense surfaces of the bicone. Unidentified optical emission bands, extended red emission, and 3.3 µm PAH emission line (of Type I) also originate close to the biconical surfaces along the X spikes (Kerr et al 1999). The spikes are clearly seen in all images, traced along the surface of the biconical outflow cavities to within the distances of 0.…”
Section: Morphologymentioning
confidence: 74%
See 1 more Smart Citation
“…Polarization maps by Perkins et al (1981) suggested that the spikes are produced by dust scattering at dense surfaces of the bicone. Unidentified optical emission bands, extended red emission, and 3.3 µm PAH emission line (of Type I) also originate close to the biconical surfaces along the X spikes (Kerr et al 1999). The spikes are clearly seen in all images, traced along the surface of the biconical outflow cavities to within the distances of 0.…”
Section: Morphologymentioning
confidence: 74%
“…At all wavelengths we observed continuum radiation from the Red Rectangle with the exception of the filter centered at 3.31 µm, where around 20-30% of the emission received is from strong line emission of polycyclic aromatic hydrocarbons (PAHs) as can be seen from spectra obtained with a 1. 2 aperture pointing at the center of the nebula (Kerr et al 1999). We presume that essentially all of the radiation in the K Brγ filter is continuum, although there may be very little of Br γ emission from the Red Rectangle observed in a 17 aperture, as is seen from spectrophotometry by Russell et al (1977).…”
Section: Reconstructed Imagesmentioning
confidence: 88%
“…For this object, Schmidt & Witt (1991) have shown that the strong optical emission features attributed to a subset of diffuse band carriers appear only at the bicone interfaces, where carbon-rich material is presumably being eroded by a bipolar plasma flow, and/or by the ultraviolet radiation from the central star. From a study of the spatial distribution and spectral structure of the 3.3 µm UIR feature, Kerr et al (1999) suggested that through this erosion the grains might produce even completely dehydrogenated DIB-emitting molecules, perhaps monocyclic carbon ring molecules (see also Kerr et al 1996). If this scenario were correct, the absence of DIBs in the outer layers of IRC + 10 • 216 could be understood as arising from the fact that its circumstellar material has not been processed at all in a similar way during its formation and ejection history.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PAH studies within extended objects reveal that the band profiles depend on distance from the illuminating star and hence the local physical conditions (Fig. 5, Kerr et al 1999;Tokunaga et al 1991;Bregman & Temi 2005;Candian et al 2012). The latter is exemplified by the dependence of the band profiles with the UV radiation field, G, and G/n e (with n e the electron density; Bregman & Temi 2005).…”
Section: E Peeters 32 Profilesmentioning
confidence: 94%